Impact of Music Therapy on Hospitalized Patients Post-Elective Orthopaedic Surgery: A Randomized Controlled Trial. (March 2018) - Gallagher, Lisa M.; Gardner, Vickie; Bates, Debbie; Mason, Shelley; Nemecek, Jeanine; DiFiore, Jacquelyn Baker; Bena, James; Li, Manshi; Bethoux, Francois
Abstract : BACKGROUND: Music therapy (MT) research has demonstrated positive effects on fatigue, depressed mood, anxiety, and pain in perioperative care areas. However, there has been limited research on the effects of MT for surgical patients on orthopaedic units. PURPOSE: The purpose of this study was to understand the impact of MT sessions on post-elective orthopaedic surgery patients' pain, mood, nausea, anxiety, use of narcotics and antiemetics, and length of stay. METHODS: This was a randomized controlled study with an experimental arm (MT sessions) and a control arm (standard medical care). Patients received MT within 24 hours of admission to the unit, as well as every day of their stay. Same-day pre- and postdata were collected 30 minutes apart for both arms, including patient self-reported mood, pain, anxiety, and nausea. Use of medications and length of stay were gleaned from the electronic medical record. RESULTS: Data were obtained for 163 patients, age 60.5 ± 11.1 years, 56% of whom were male. Joints targeted by surgeries were hips (54%), knees (42%), and shoulders (4%). There were significantly greater changes favoring the MT group on Day 1 (pain, anxiety, and mood), Day 2 (pain, anxiety, mood, and nausea), and Day 3 (pain, anxiety, and mood). Among participants with a pre–pain score of 2 or more on Day 1, a decrease of at least 2 points was noted in 36% of the MT group and 10% of the control group ( P < .001). Overall, 73% of MT patients versus 41% of control patients reported improved pain ( P < .001). No significant between-group differences in medications or length of stay were noted. CONCLUSIONS: We observed greater same-day improvements of pain, emotional status, and nausea with MT sessions, compared to usual care, in patients hospitalized after elective orthopaedic surgeries. Effects on narcotic and antiemetic usage, as well as length of stay, were not observed. More research needs to be conducted to better understand the benefits of MT pre- and post-elective orthopaedic surgery.